MODERNIZATION OF SOLAR AND WIND RENEWABLE ENERGY STATIONS IN UZBEKISTAN (Multidisciplinary Journal of Science and Technology, 2025)
Uzbekistan’s energy sector is overwhelmingly fossil‑fuel based. In 2019, natural gas accounted for over 90% of primary energy production. Electricity generation has similarly relied on thermal power (gas/coal) and hydropower; renewables beyond hydro were negligible until recently. Total domestic energy supply in 2019 was about 47.1 Mto, with oil and coal contributing the remainder and hydropower about 1%. In practice, renewables (solar, wind, hydro, bio) provided roughly 10% of electricity in 2019 and early 2020.